Inovasi dalam Bisnis Halal - St. Rahma (Alkasb: Journal of Islamic Economics, 2023)
Innovation means finding something new or making various updates in the form of products, ideas, designs, and so on. One of the most important characteristics of a business is its ability to innovate. The halal industry is one of the businesses that is experiencing very fast development in Indonesia. This refers to high public awareness of the importance of using products that are guaranteed to be safe (halal). The method used in this study uses a library method or approach(library research). The data collected is secondary data that comes from various sources, both print and electronic. From this discussion it can be concluded that, seeing the government's increasingly intensive efforts to advance the halal industry, now many business people have started to play a role in advancing the Indonesian halal industry. One of the innovations in the halal business is the Muslim fashion brand Noore. Blending conceptssportswear comfortable and elegant design, loose cut and slightly silhouetted, really meet the needs of Muslim women to choose a comfortable hijab for exercising. Noore develops patterns and product designs so that women who wear hijab can wear beautiful clothes, but still be polite.